2020
DOI: 10.1029/2019jb019108
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Fluid Flow in Shallow Crustal Fault Zones: 2. Insights From Cross‐Hole Forced Flow Experiments in Damage Zones

Abstract: Cross-hole fluid injection tests were performed on shallow (0.5 km depth) crustal fault zones to characterize their internal flow structures on scales of 3-30 m. The data were acquired at the Grimsel Rock Laboratory, Switzerland, after the zonal isolation of damage zones in boreholes equipped with multipacker systems. We show that 80% of the pressure responses detected evolved as a power function of time due to fracture-controlled flow and were best described by a fractional model with a flow dimension (n) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…Similar fractures have been reported for parallel, low‐displacement (<10 m) faults separated by a few meters (Martel et al, , Figure 3a), and extensive field studies have identified and characterized linking damage zones from exhumed faults (Kim et al, ). If permeable, such damage zones may allow fluids to migrate across subparallel faults and play a key role in promoting fault‐controlled flow (Brixel et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar fractures have been reported for parallel, low‐displacement (<10 m) faults separated by a few meters (Martel et al, , Figure 3a), and extensive field studies have identified and characterized linking damage zones from exhumed faults (Kim et al, ). If permeable, such damage zones may allow fluids to migrate across subparallel faults and play a key role in promoting fault‐controlled flow (Brixel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For initial characterization, we deployed temporary straddle packer systems to screen the main structures identified from borehole image logs. This survey informed the final design of the pressure monitoring boreholes by defining the position and length of permanent observation intervals (for cross‐hole testing, see Brixel et al, ). Once completed, the downhole installation of 0.2‐m‐long packer seats and epoxy resin sections enabled recording fluid pressure in eight intervals in dedicated pressure monitoring boreholes.…”
Section: Datamentioning
confidence: 99%
“…The ISC experiment volume and its fracture network are fluid-saturated. Fluid flow was shown to be primarily fault-controlled in well testing experiments by Brixel et al [13], who found permeability to be strongly decreasing (from 10 −13 m 2 to 10 −21 m 2 ) within 1 m to 5 m from the fault cores. Brixel et al [12] determined the equivalent hydraulic apertures of single fractures in the rock volume to range from 2 to 130 µm, with a mean of 30 µm.…”
Section: Isc Experiments At the Grimsel Test Sitementioning
confidence: 97%
“…Therefore, additionally to the monitoring performed during the stimulations, pre-and post-stimulation characterizations were carried out with various geological, hydrogeological, and geophysical methods. Aside from GPR, as described here, by Giertzuch et al [30] and by Doetsch et al [39], extensive hydrologic testing was performed, tracer tests were run, and borehole logs were acquired, e.g., [7,12,13,38,[40][41][42][43].…”
Section: Isc Experiments At the Grimsel Test Sitementioning
confidence: 99%
See 1 more Smart Citation